RESPON ANGGOTA KELOMPOK TANI TERHADAP PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) DI KECAMATAN KEBUN TEBU KABUPATEN LAMPUNG BARAT - Hilman Budianto; Sumaryo Gitosaputro; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This research aimed to assess the response of farmers group member towards PUAP program in Kebun Tebu District; investigate the factors related to farmer's response towards the implementation of the PUAP Program in Kebun Tebu District; know the suitability between the planning and implementation of PUAP Program. The research was conducted in Pekon Cipta Mulya, Kebun Tebu District, West Lampung Regency. The population of this research were all farmers who take part in RADP in Kebun Tebu District. The sample of this research were 100 farmers who became member of Gapoktan Mulya Mandiri in Pekon Cipta Mulya which choosen using cluster sampling method. The research data collection was conducted from August until September 2015. The research data wascolleceted by questionnaire and anylized by descriptive analysis method. The results of this research showed thatt the response of farmers group member categorized as quite good. factors related to farmer’s response towards the implementation of PUAP Program were the level of formal education of farmers, farmers' knowledge, motivation of farmers joint in PUAP Program and farmers’ farming experience. There have been a suitability between the planning and implementation of the PUAP Program in Pekon Cipta Mulya but practically PUAP program still needed to be developed in order to touch the whole subsystem agribusiness.Key words: PUAP/RADP, response, subsystem agribusiness This research aimed to assess the response of farmers group member towards PUAP program in Kebun Tebu District;  investigate the factors related to farmer's response towards the implementation of the PUAP Program in Kebun Tebu District; know the suitability between the planning and implementation of PUAP Program.  The research was conducted in Pekon Cipta Mulya, Kebun Tebu District, West Lampung Regency. The population of this research were all farmers who take part in RADP in Kebun Tebu District.  The sample of this research were 100 farmers who became member of Gapoktan Mulya Mandiri in Pekon Cipta Mulya which choosen using cluster sampling method. The research data collection was conducted from August until September 2015. The research data wascolleceted by questionnaire and anylized by descriptive analysis method. The results of this research showed thatt the response of farmers group member categorized as quite good. factors related to farmer’s response towards the implementation of PUAP Program were the level of formal education of farmers, farmers' knowledge, motivation of farmers joint in PUAP Program and farmers’ farming experience.  There have been a suitability between the planning and implementation of the PUAP Program in Pekon Cipta Mulya but practically PUAP program still needed to be developed in order to touch the whole subsystem agribusiness. Key words: PUAP/RADP, response, subsystem agribusiness